MPTP Impairs Dopamine D1 Receptor-Mediated Survival of Newborn Neurons in Ventral Hippocampus to Cause Depressive-Like Behaviors in Adult Mice - Zhang, Tingting; Hong, Juan; Di, Tingting; Chen, Ling (Frontiers in Molecular Neuroscience, 2016)
Parkinson’s disease is characterized by motor symptoms with depression. We evaluated the influence of dopaminergic depletion on hippocampal neurogenesis process to explore mechanisms of depression production. Five consecutive days of MPTP injection in mice (MPTP-mice) reduced dopaminergic fibers in hippocampal dentate gyrus (DG). MPTP-mice exhibited depressive-like behaviors for 2-3 weeks later. BrdU was injected at 4 hrs after last-injection of MPTP. BrdU+ cells in dorsal (d-DG) and ventral (v-DG) DG were examined on day 1 (D1), 7 (D7), 14 (D14) and 21 (D21) after BrdU injection. Fewer D7-, D14- and D21-BrdU+ cells or BrdU+/NeuN+ cells, but not D1-BrdU+ cells, were found in v-DG of MPTP-mice than in controls. However, the number of BrdU+ cells in d-DG did not differ between the both. Loss of doublecortin-positive (DCX+) cells was observed in v-DG of MPTP-mice. PKA and CREB phosphorylation were reduced in v-DG of MPTP-mice, which were reversed by D1R agonist SKF38393, but not D2R agonist quinpirole. The treatment of MPTP-mice with SKF38393 on days 2-7 after BrdU-injection reduced the loss of D7- and D21-BrdU+ cells in v-DG and improved the depressive-like behaviors; these changes were sensitive to PKA inhibitor H89. Moreover, the v-DG injection of SKF38393 in MPTP-mice could reduce the loss of D21-BrdU+ cells and relieve the depressive-like behaviors. In control mice, the blockade of D1R by SCH23390 caused the reduction of D21-BrdU+ cells in v-DG and the depressive-like behaviors. Our results indicate that MPTP-reduced dopaminergic depletion impairs the D1R-mediated early survival of newborn neurons in v-DG, producing depressive-like behaviors.